Revitalizing the Sri Lankan Economy: An In-Depth Exploration of Gastro Tourism as a Catalyst for Upliftment – Visitor Perspective - Lokeshwara, Anuja Akalanka; Jayarathne, Ruchiranga; Kothalawala, Charuka (Centre For Tourism Planning and Development, 2024)
This paper explores the transformative potential of Gastro Tourism in Sri Lanka, assessing its ability to attract visitors and stimulate economic growth through the rich tapestry of culinary diversity. This study investigates the personal meanings associated with gastro tourism experiences by utilizing qualitative methods to gather and analyze insights from a diverse cohort of Sri Lankan-bound tourists. The purposive sampling tech2ique ensures a comprehensive understanding, incorporating individuals with extensive knowledge of Sri Lankan food culture and exposure to global gastronomy. The data collection technique involves in-depth interviews, allowing for a nuanced exploration of participants’ perspectives on Sri Lankan cuisine and gastro tourism. To ensure trustworthiness, the study adheres to Tracy’s (2010) criteria, emphasizing credibility, transferability, dependability, and confirmability. Thematic analysis is employed for data analysis, revealing five interconnected themes: Economic Transformation Through Culinary Experiences, Empowerment of Entrepreneurs and Small Businesses, Cultural Diplomacy Driving Economic Integration, Holistic Development, and Sustainable Growth and Rural Economic Upliftment. The thematic analysis underscores the multifaceted impact of gastro tourism on Sri Lanka’s economic resurgence, portraying it as a catalyst for economic vibrancy, entrepreneurship, cultural diplomacy, holistic development, and sustainable practices.